PENGARUH KOMPETENSI, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI MANAJEMEN RSUD TEUKU UMAR KABUPATEN ACEH JAYA - Presilawati, Febyolla; Fitri, Aida; Phonna, Hilwa Putri (Fakultas Ekonomi, 2024)
This study aims to determine the Influence of Competence, Work Motivation, Job Satisfaction on the Performance of Management Employees at Teuku Umar Hospital, Aceh Jaya Regency. This study uses a quantitative method, the sample size used in this study was 60 respondents. Research data were collected through a list of questions/questionnaires and documentation studies to determine whether each variable affects the productivity of Management Employees at Teuku Umar Hospital, Aceh Jaya Regency. The Influence of Competence, Work Motivation, Job Satisfaction, on Employee Performance has a positive effect on the productivity of Management Employees at Teuku Umar Hospital, Aceh Jaya Regency.Keywords: Competence, Work Motivation, Job Satisfaction, Employee Performance